Association between dietary patterns and the prognosis of amyotrophic lateral sclerosis in China: a cross-sectional study - Xu, Xun; Huang, Yuwei; Zhu, Yue; Jin, Qingwen (Frontiers in Nutrition, 2024)
Recently, a growing number of studies have specifically examined the impact of dietary variables on the development and progression of ALS. The purpose of this study was to investigate the correlation between different dietary patterns and Chinese ALS patients' prognosis. A retrospective study was conducted by recruiting 590 patients with ALS who attended and were regularly followed at hospitals in Nanjing from 2016 to 2023. Nutrient intake was calculated using dietary information collected through the food frequency questionnaire (FFQ), and patients were divided into a control group and special diet groups, including a high-calorie group (HC), a high-protein group (HP), and a ketogenic diet group (KD), based on their specific intake. Patients in the HP had a better nutritional status. And the disease progression rate (ΔFS) was significantly associated with dietary patterns, with the KD group having the lowest ΔFS. Meanwhile, special diets extended the survival time of stage 4 patients but had no effect on the overall survival of the disease. Therefore, a special diet can be one of effective options for patients with advanced ALS. Patients with poor nutritional status may choose the HP diet, whereas those with underlying conditions should consider the ketogenic diet with caution.